Sistema APPCC aplicado à farinha de trigo integral - Perseguelo, Franciele Maria (2016)
In recent years the search for healthier eating habits is growing gradually and the choice of whole grain foods is included in this trend. Wheat as a source of dietary fiber has been used in the form of wheat bran, whole wheat flour or as part of the composition of whole wheat bread and pasta. However, so far, few alerts are raised regarding the contaminants in the external portions of the grain, and the possibility of the processing reduces these contaminants to acceptable levels. In this research project, hazard characteristics were investigated in the grain and/or processing, through the systematic applied worldwide and known as Hazard Analysis and Critical Control Points (HACCP). The project was developed in a wheat mill where the Good Manufacturing Practices (GMP) and Integrated Pest Management (IPM) were already implemented.The HACCP methodology was developed after review of Prerequisite Programs, detailed description of the production process and exploratory/confirmatory analysis at strategic points, then moving to the application of the seven theoretical System Principles. The results of exploratory analyzes found that processing steps removed most of the contaminants in wheat, yielding a whole wheat flour with safe physical, chemical and microbiological parameters, in accordance with current legislation. The Hazard Analysis and Control Point Critical system were applied to the production of whole wheat flour, it was found that the processing reduces contaminants in wheat at acceptable levels, provided that the three points of control present in sieving (Turbo Sieve) and transport (filter and Metal Detectors) are monitored properly. In the decision-tree approach was not found critical control points (CCP) for wheat storage.